(1→3)-α-d-Glucan from Fruiting Body and Mycelium of Cerrena unicolor (Bull.) Murrill: Structural Characterization and Use as a Novel Inducer of Mutanase. (16th February 2017) - Osińska-Jaroszuk, Monika; Wiater, Adrian; Choma, Adam; Pleszczyńska, Małgorzata; Jaszek, Magdalena; Janusz, Grzegorz; Skowronek, Marcin; Szczodrak, Janusz
Abstract : Water-insoluble, alkali-soluble polysaccharide (marked as ASP) was extracted from the vegetative mycelium and fruiting body of Cerrena unicolor strain. Monosaccharide examination of ASP demonstrated that the isolated biopolymer was composed mainly of glucose, xylose, and mannose monomers. The methylation investigation of studied polymers indicated that (1→3)-linked α -d -Glc p is the major chain constituent (92.2% for glucans isolated from fruiting body and 90.1% from mycelium). 1 H NMR, FT-IR, and immunofluorescent labelling determinations confirmed that the polysaccharides isolated from both fruiting body and mycelium of C . unicolor are (1→3)-α -d -glucans. The obtained (1→3)-α -d -glucans showed differences in viscosity and similar characteristics in optical rotations. (1→3)-α -d -Glucans extracted from mycelium and fruiting body of C. unicolor were also used as potential and specific inducers of mutanase synthesis by Trichoderma harzianum . The highest mutanase activity (0.38 U/mL) was obtained after induction of enzyme by (1→3)-α -d -glucan isolated from the mycelium of C. unicolor, and this biopolymer has been suggested as a new alternative to streptococcal mutan for the mutanase induction in T. harzianum . (1→3)-α -d -Glucan-induced mutanase showed high hydrolysis potential in reaction with dextranase-pretreated mutan, where maximal degree of saccharification and solubilization of this bacterial homoglucan (83.1% and 78.4%, resp.) was reached in 3 h at 45°C.